Stroke admissions and revascularization treatments in Denmark during COVID‐19. (3rd October 2021) - Drenck, Nicolas; Grundtvig, Josefine; Christensen, Thomas; Iversen, Helle Klingenberg; Kruuse, Christina; Truelsen, Thomas; Wienecke, Troels; Christensen, Hanne
Abstract: Objective: The aim of this study was to assess the number of stroke‐related admissions and acute treatments during the first two waves of COVID‐19 and lockdowns in the Capital Region of Denmark and the Region of Zealand. Materials & Methods: The weekly numbers of admitted patients with stroke were retrieved from electronic patient records from January 2019 to February 2021 and analysed to reveal potential fluctuations in patient volumes during the pandemic. Results: A total of 23, 688 patients were included, of whom 2049 patients were treated with tissue‐type plasminogen activators (tPA) and 552 underwent endovascular thrombectomy (EVT). We found a transient decrease in the number of weekly admitted patients (pts/week) with all strokes (−9.8 pts/week, 95% CI: −19.4; −0.2, p = .046) and stroke mimics (−30.1 pts/week, 95% CI: −39.9; −20.3, p < .001) during the first lockdown compared to pre‐COVID‐19. The number of subarachnoid haemorrhage, intracerebral haemorrhage, and ischaemic stroke admissions showed insignificant declines. Analysing all COVID‐19 periods collectively revealed increased volumes of ischaemic stroke (+6.2 pts/week, 95% CI: +1.6; +10.7, p = .009) compared to pre‐COVID levels, while numbers of stroke mimics remained lower than pre‐COVID. Weekly tPA and EVT treatments remained constant throughout the study period. Conclusions: Our results are comparable with other studies in finding reductions in stroke‐related admissions early in the pandemic. This is the first study to report increased stroke volumes following the first wave of the pandemic. The mechanisms behind the observed drop and subsequent rise in strokes are unclear and warrant further investigation.